International comparisons of nominal and real construction labour productivity. Issue 7 (1st August 2018) - Chia, Fah Choy; Skitmore, Martin; Gray, Jason; Bridge, Adrian
Abstract : Purpose: A comparison of international construction labour productivity (CLP) is carried out by the conventional use of exchange rates to convert national construction output to a common base currency. Such measurement is always distorted by price-level differences between countries and therefore the purpose of this paper is to adopt a purchasing power parities (PPPs) approach, which eliminates price-level differences, as an alternative means of comparing CLP. Design/methodology/approach: PPP construction expenditure data from the World Bank's International Comparison Programme 2011 and employment statistics maintained by the International Labour Organization are used to generate the CLP of 93 matching economies. A one-way analysis of variance is conducted to evaluate the relationship between the development status and the CLPs. Findings: The CLPs of developed economies are higher than developing economies in both PPPs (real) and exchange rate (nominal) measurements. The real CLPs are always higher than nominal CLP in high-income, upper-middle-income, lower-middle-income and low-income economies. Both real and nominal CLPs converge along with the economic growth. Research limitations/implications: The average figures used in the study may not always be the most representative statistics. The CLPs determined provide an initial approximation for comparison between different economies to gain further insights into the best practices and policies for the more successful economies. Future research is recommended to uncover the underlying factors of CLPs congruence. Originality/value: The convergence of real and nominal CLPs when economies transit from a developing to developed status indicates that the construction product has transformed from a commonly understood non-internationally traded product to an internationally traded product.